The effect of different transport distances and season on meat quality characteristics of broiler chicken in commercial slaughter conditions - Teke, Bülent; Çobanbaşı, Yavuz (My University)
The aim of the study was to determine the effect of season and transport distance on meat quality characteristics of broiler chicken in commercial transport and slaughter conditions. The study was carried out on Ross 308 broiler chickens reared under similar commercial conditions from three different seasons (summer, autumn and winter) and three different transport distances (40 km, 70 km and 130 km). Meat samples were taken on July, October, and December for summer, autumn and winter seasons, respectively during 2018. Broilers in trucks were waited in holding barn for 1 h. A total of 135 broilers, 15 samples per transport distance, were randomly selected to determine meat quality characteristics, (3 seasons × 3 transport distances × 15 samples). Meat colour parameters, pH4h, drip loss, cooking loss and Warner Bratzler shear force (WBSF) was determined. In winter, pH4h, a*24h and b*24h were higher than other seasons, while L*24h, drip loss and WBSF were lower than other seasons. The incidence of PSE (pale, soft, exudative) meat was the highest in summer (26.67%), while the incidence of DFD (dark, firm, dry) meat was the highest in winter (53.33%). The lowest incidence of normal breast meat was in winter season. In conclusion, incidence of normal breast meat decreased when broiler chickens were transported in winter. However, incidence of PSE meat was the highest in summer season. Transport distance affected adversely the some meat quality characteristics and this effect was most pronounced in summer season. In order to improve the meat quality, as much as possible, transportation of broiler chickens should be carried out within thermal comfort zone ranges and in short distance transport.

Bu araştırma ticari nakil ve kesim koşullarında etlik piliçlerin et kalite özellikleri üzerine mevsimin ve nakil mesafesinin etkisini belirlemek amacıyla yapılmıştır. Bu araştırma benzer ticari koşullar altında yetiştirilen 3 farklı mevsim (yaz, sonbahar ve kış) ve 3 farklı nakil mesafesinde (40 km, 70 km ve 130 km) kesimhaneye nakledilen Ross 308 hattı etlik piliçler üzerinde yürütülmüştür. Et örnekleri 2018 yılında yaz, sonbahar ve kış mevsimleri için sırasıyla Temmuz, Ekim ve Aralık aylarında alınmıştır. Etlik piliçlere nakil aracı içinde 1 saat dinlenme süresi uygulanmıştır. Her mevsimde her bir nakil mesafesi için 15’er örnek olmak üzere toplam 135 etlik piliç (3 mevsim × 3 nakil mesafesi × 15 örnek) et kalite özelliklerinin belirlenmesi için rastgele seçilmiştir. Et rengi, pH4h, damlama kaybı, pişirme kaybı ve Warner Bratzler kesme kuvveti (WBSF) belirlenmiştir. Kış mevsiminde pH4h, a*24h ve b*24h değeri diğer mevsimlerden daha yüksek iken L*24h, damlama kaybı ve WBSF değeri diğer mevsimlerden daha düşük bulunmuştur. PSE (soluk, yumuşak, sulu) etin insidensi yaz mevsiminde en yüksek iken (%26.67), DFD (koyu, sert, kuru) etin insidensi ise kış mevsiminde en yüksek olarak tespit edilmiştir (%53.33). En düşük normal et insidensi kış mevsiminde bulunmuştur. Sonuç olarak, kış mevsiminde etlik piliçlerin nakli normal et insidensinin düşmesi ile sonuçlanmıştır. Diğer taraftan, PSE etin insidensi ise en yüksek yaz mevsiminde bulunmuştur. Nakil mesafesinin artışı bazı et kalite özelliklerini olumsuz olarak etkilemiş ve en çok bu etki yaz mevsiminde gözlenmiştir. Etlik piliçlerin et kalite özelliklerinin olumsuz olarak etkilenmemesi için özellikle yaz mevsiminde uzun mesafe nakillerden kaçınmak ve termal konfor zonu aralıklarında naklin yapılması önerilmektedir.
Ticari kesim koşullarında etlik piliçlerde farklı nakil mesafelerinin ve mevsimin et kalitesine etkisi
Keywords: Animal Welfare; DFD Meat; Meat Quality; PSE Meat; Transportation; DFD Et; Et Kalitesi; Hayvan Refahı; Nakil; PSE Et